Qualidade do manejo no frigorífico: efeitos no bem-estar animal e na qualidade da carcaça e da carne - Barreto, Emília Rodrigues de Lima [UNESP] (2014)
The aim of this study was to evaluate the association between beef cattle, pre-slaughter handling, animal welfare and carcass quality besides testing the applicability of an index that assess the handling quality in slaughterhouses. The study was carried out in three plants licensed to export meat located in the southeast of Brazil, assessing 42,360 cattle. One indicator of animal welfare (falls) and two indicators of handling quality (animals hit by gates and electric prod use) were recorded. These indicators were used to calculate the Handling Quality Scores (HQS). The occurence of bruises and meat pH were also recorded as indicators of carcass and meat quality. The occurence of carcasses with multiple bruises (at least three), meat with high pH (≥ 5,9), and the occurrence of emergency slaughter and acts of abuse (trampled animals and non-ambulatory animals being drove inappropriately) were also recorded. For control purposes the following handling information were also recorded: periods of day, cattle category and different cattle categories being handled together. Data was analyzed by Generalized Linear Models and Pearson Correlation by using the GLM and CORR procedures of SAS program. It was also performed Chi-squared test and Principal Components Analysis (PCA). There was a significant effect (P<0.01) of animal welfare indicators and handling indicators on the HQS in the three plants. The highest and lowest HQS values were observed in plants 3 and 1, respectively. HQS values increased in all plants when acts of abuse occurred during handling (P<0.01). It was also observed an effect (P<0.01) of the periods of day with increasing values of HQS and frequency of falls, electric prod use and animals hit by gates throughout the working day in all plants. Cattle categories and different cattle categories being handled influenced (P <0.01) HQS. The correlation analysis showed a strong ...